Argininosuccinic aciduria fosters neuronal nitrosative stress reversed by Asl gene transfer - Julien Baruteau (Nature Portfolio, 2018)
Patients with mutations in the ASL gene present with argininosuccinic aciduria characterised by hyperammonaemia and cognitive impairment. Here, the authors show that cerebral disease involves neuronal nitrosative/oxidative stress that is not induced by hyperammonaemia, and that it can be reversed using AAV-ASL directed to liver and brain in mice.